Degradable recycled fluorescent polyacetals and methods of making the same
By controlling the polyacetal reaction through an acid-base synergistic catalytic system, the problem of low molecular weight in traditional methods is solved, and high molecular weight polyacetals with fluorescent properties are prepared, which are suitable for high-end applications.
Patent Information
- Application Number
- CN202610402148.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-30
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-03-30
AI Technical Summary
Traditional direct acetalization methods are difficult to prepare high molecular weight polyacetals because the acid sensitivity of acetal bonds limits the chain growth process, resulting in products with low molecular weight and wide dispersion coefficients, which are difficult to meet the material performance requirements of high-end applications.
An acid-base synergistic catalytic system is employed, in which the carbonyl group is activated by an acidic component and the acidity of the reaction microenvironment is adjusted by an alkaline buffer to construct a dynamic equilibrium catalytic environment, control the polymerization kinetics, and inhibit the acid-catalyzed degradation and reverse hydrolysis of the acetal backbone.
The preparation of high molecular weight and well-defined polyacetal materials has been achieved, which possess non-traditional fluorescent properties, require no additional fluorophores, and are suitable for fields such as chemical sensing, anti-counterfeiting labels, and optoelectronic displays.
Smart Images

Figure CN122037098B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fluorescent polyacetal technology, specifically to a biodegradable and recyclable fluorescent polyacetal and its preparation method. Background Technology
[0002] Polyacetals are a class of polymeric materials with repeating acetal bonds in their main chain structure. Due to their excellent biodegradability, chemical recycling ability, and superior mechanical strength, they have significant application value in fields such as green packaging, biomedical engineering, and high-performance engineering plastics. These materials are typically prepared by the condensation reaction of biomass-derived diols and aldehyde monomers, meeting the current urgent needs of the chemical industry for sustainable and environmentally friendly materials.
[0003] In existing synthetic techniques, direct acetalization is one of the main routes for preparing polyacetals. This method typically uses a protic acid or Lewis acid as a catalyst to induce nucleophilic addition and dehydration reactions between the diol and the aldehyde under heating conditions. Water, a byproduct generated during the reaction, is removed physically to shift the chemical equilibrium towards polymer formation, thereby constructing a linear polymer chain. Due to its high atom economy, simple reaction route, and wide range of applicable monomers, direct acetalization is widely used in the development and production of related materials.
[0004] However, the traditional direct acetalization method has a significant technical drawback in practical applications: it is difficult to prepare high molecular weight polyacetal products. This is because the acetal bond itself has high acid sensitivity. While a single acidic catalyst drives the polymerization reaction, the active acid sites in the reaction system also catalyze the acidolysis or reverse hydrolysis of the already formed polymer backbone. This associated degradation side reaction is particularly intense in the later stages of the reaction or at high temperatures, which severely restricts the chain growth process. The final product usually has a low molecular weight and a wide dispersion coefficient, making it difficult to meet the material performance requirements of high-end applications. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a biodegradable and recyclable fluorescent polyacetal and its preparation method, thus solving the problems mentioned in the background section.
[0006] To achieve the above objectives, the present invention provides the following technical solution: Firstly, the present invention provides a biodegradable and recyclable fluorescent polyacetal, employing the following technical solution: A biodegradable and recyclable fluorescent polyacetal, wherein the polyacetal is polymerized from raw materials comprising the following components under acid-base synergistic catalysis: component A is a hydroxyl-containing polyol, whose molecular structure contains at least two hydroxyl groups; component B is an aldehyde-containing compound, whose molecular structure contains at least one aldehyde group; the catalyst system consists of an acid catalyst and an alkaline buffer. The molar ratio of the hydroxyl groups in component A to the aldehyde groups in component B is 1–50 : 1–25; the amount of the acid catalyst is 0.01 wt%–5 wt% of the total mass of the reaction system; the molar ratio of the acid catalyst to the alkaline buffer is 5–100 : 1–10000.
[0007] By employing the above technical solution, this invention resolves the competition between chain growth and chain degradation in traditional acetal polymerization using an acid-base synergistic catalytic system, thereby obtaining polyacetal materials with high molecular weight and well-defined structures. Its core mechanism lies in constructing a dynamically balanced catalytic environment driven by acid and buffered by base: Carbonyl activation and chain initiation: The acidic component (protic acid or Lewis acid) in the system first coordinates or protonates with the carbonyl oxygen atom of the aldehyde group in component B, reducing the electron cloud density of the carbonyl carbon and enhancing its electrophilicity. This allows the hydroxyl group in component A to nucleophilically attack the carbonyl carbon with a lower activation energy, forming an acetal bond (-O-CHR-O-) through an addition-elimination reaction, thereby initiating the polymerization reaction and driving chain growth.
[0008] Microenvironment acidity regulation and chain stability: Acetal bonds are inherently acid-sensitive chemical bonds, easily protonated and broken in strongly acidic media (i.e., acidolysis side reaction). Basic buffers introduced into the system (such as organic amines, nitrogen-containing heterocycles, etc.) act as proton acceptors or Lewis bases, establishing acid-base equilibrium with the acidic catalyst and regulating the effective acidity of the reaction microenvironment in situ. Basic components can neutralize or shield excessively high local free acid activity, inhibiting acid-catalyzed breakage of the already formed long-chain polyacetal backbone.
[0009] Polymerization kinetic selectivity: By controlling a specific acid-base molar ratio (5–100 : 1–10000), the system maintains the acid strength of the reaction medium within a specific kinetic window. Within this window, the forward reaction rate of monomer conversion to polymer is significantly higher than the reverse reaction rate of polymer acidolysis, thereby maintaining the stability of the polymer chain and achieving continuous molecular weight growth during long-term high-temperature polymerization. Furthermore, due to the dense oxygen atoms and spatially folded structure in the main chain, this specific polyacetal material can generate non-traditional fluorescence through spatial conjugation or electron clustering effects, achieving photoluminescence without the need to introduce additional large conjugated fluorophores.
[0010] Preferably, component A is selected from one or a combination of several aliphatic diols, aromatic diols, heteroatom-containing diols, or polyether diols; component B is selected from one or a combination of several aliphatic aldehydes, aromatic aldehydes, or heterocyclic aldehydes. By adopting the above preferred scheme and flexibly selecting monomers with aliphatic, aromatic, or heterocyclic structures, the glass transition temperature, mechanical strength, and optical properties of the polymer can be adjusted. In particular, the introduction of aromatic or heterocyclic side groups can utilize the electronic effects of the side groups to adjust the electronic energy level of the acetal oxygen atom, thereby adjusting the fluorescence emission wavelength from the blue light region to the orange-red light region, achieving full-spectrum fluorescence modulation.
[0011] Preferably, the polyacetal has a number-average molecular weight of 1000–50000 g / mol and exhibits fluorescence emission wavelengths of 350 nm–680 nm under 365 nm excitation light. By adopting the above preferred embodiment, this molecular weight range ensures that the material has good film-forming properties and mechanical properties, while the wide range of fluorescence characteristics makes it suitable for fields such as anti-counterfeiting labels and bio-imaging.
[0012] Secondly, the present invention provides a method for preparing the above-mentioned biodegradable and recyclable fluorescent polyacetal, employing the following technical solution: A method for preparing a biodegradable and recyclable fluorescent polyacetal includes the following steps: (1) Feeding and mixing: Mixing component A and component B evenly; (2) Catalyst addition: Adding the acid catalyst and the alkaline buffer to the mixing system in step (1); (3) Polymerization reaction: Heating the reaction system to 20°C to 200°C under stirring conditions for 10 min to 72 h, and removing the by-product water during the reaction; (4) Post-treatment: After the reaction is completed, adding an alkaline solution to adjust the pH of the reaction solution to neutral, and obtaining the target product after washing, extraction, drying and vacuum distillation.
[0013] By adopting the above technical solution, the preparation method is simple and has strong universality.
[0014] Water removal-driven equilibrium: The acetalization reaction is a reversible equilibrium reaction. By continuously removing byproduct water under heating conditions (such as through azeotropic distillation or molecular sieve adsorption), according to Le Chatelier's principle, the chemical equilibrium can be continuously disrupted, driving the reaction toward the formation of polyacetal, thereby improving monomer conversion and product yield.
[0015] Post-treatment stabilization: An alkaline solution is added immediately after the reaction to adjust the pH to neutral, which can quickly quench the acidic catalytic activity in the system and prevent polymer degradation caused by residual acid during cooling or subsequent treatment, ensuring that the molecular weight of the final product remains consistent with that at the reaction endpoint.
[0016] Preferably, in step (3), the polymerization reaction is carried out in an inert gas atmosphere composed of argon or nitrogen. By adopting the above preferred scheme, the inert gas atmosphere effectively isolates oxygen, prevents aldehyde monomers from being oxidized into carboxylic acids at high temperatures (carboxylic acids will disrupt the acid-base balance and terminate the polymerization), and also avoids oxidative crosslinking of the polymer backbone and side groups or destruction of chromophores, thus ensuring the high purity and excellent fluorescence quantum yield of the product.
[0017] Thirdly, the present invention provides a method for degrading and recycling the above-mentioned degradable and recyclable fluorescent polyacetal, employing the following technical solution: A method for degrading and recycling fluorescent polyacetal includes the following steps: immersing the polyacetal in an acidic aqueous solution or an aqueous organic solution with a concentration of 0.01 M to 1 M for degradation; and after degradation, extracting and recovering component A and component B using an organic solvent.
[0018] By employing the above technical solution, this invention achieves a closed-loop chemical cycle for polymer materials. The mechanism lies in utilizing the responsive switching of acetal bonds to acidic environments: Excess acid triggers depolymerization: Although acid catalysts are used in the synthesis process, the degradation process completely disrupts the acid-base buffer balance during synthesis by introducing an excess of strong acid (0.01 M to 1 M) and a large amount of water. The high concentration of protons rapidly attacks the acetal oxygen atoms on the polymer backbone, protonating them to form oxonium ion intermediates.
[0019] Hydrolysis equilibrium shift: In the presence of abundant water, oxonium ions readily break down and react with water molecules to form hemiacetals, which eventually decompose into the original diols and aldehydes. Because the water concentration is much higher than during polymerization, the reaction equilibrium shifts entirely towards hydrolysis, causing the polymer chains to rapidly disintegrate into smaller monomer molecules.
[0020] Monomer recovery: The degradation products are thermodynamically stable raw material monomers that have not undergone irreversible chemical modification. Therefore, they can be separated and recovered through simple extraction and distillation operations with a high recovery rate. They can be reused in polymerization, which meets the requirements of green chemistry and sustainable development.
[0021] This invention provides a biodegradable and recyclable fluorescent polyacetal and its preparation method. It has the following beneficial effects: 1. This invention achieves precise control of polymerization kinetics by constructing an acid-base synergistic catalytic system, utilizing acidic components to activate carbonyl groups to initiate nucleophilic addition, and employing an alkaline buffer to adjust the effective acidity of the reaction system in situ. This mechanism effectively suppresses acid-catalyzed degradation and reverse hydrolysis side reactions of the acetal backbone at high temperatures, overcoming the technical bottlenecks of low molecular weight and wide dispersibility of products from traditional direct acetalization methods. It enables the efficient preparation of high molecular weight polyacetal materials with well-defined structures and controllable molecular weights under mild conditions.
[0022] 2. This invention establishes a closed-loop recycling mechanism for the entire life cycle of polymers by utilizing the acid-responsive chemical properties of acetal bonds. The resulting polyacetal material remains stable during the synthesis stage, but can rapidly undergo complete depolymerization under specific acidic hydrolysis conditions, reducing it to the initial diol and aldehyde monomers. This degradation process is thorough and produces no highly toxic byproducts. High-purity recovery and recycling of raw materials can be achieved through conventional solvent extraction and distillation, significantly reducing the dependence of polymer materials on fossil resources and the environmental burden.
[0023] 3. This invention achieves intrinsic fluorescence functionalization of non-conjugated polyacetal materials through molecular structure design. Utilizing the spatial clustering effect of oxygen atoms in the main chain acetal and the electronic push-pull effect of side groups, visible light emission covering the wavelength range of 350 nm to 680 nm can be obtained simply by changing the type of aldehyde monomer, without introducing additional expensive fluorophores or large conjugated structures. This full-spectrum fluorescence modulation characteristic, combined with the material's processability, gives it significant application advantages in high-value-added fields such as chemical sensing, anti-counterfeiting labeling, and optoelectronic displays. Attached Figure Description
[0024] Figure 1 The specific preparation reaction formula of this invention; Figure 2 This is the degradation reaction formula of the present invention; Figure 3 The hydrogen NMR spectrum of the target product P1 in Example 1 of this invention; Figure 4 The hydrogen NMR spectrum of the target product P2 in Example 2 of this invention; Figure 5 The hydrogen NMR spectrum of the target product P3 in Example 3 of this invention; Figure 6 The hydrogen NMR spectrum of the target product P4 in Example 4 of this invention; Figure 7 The hydrogen NMR spectrum of the target product P5 in Example 5 of this invention; Figure 8 The hydrogen NMR spectrum of the target product P6 in Example 6 of this invention; Figure 9 The hydrogen NMR spectrum of the target product P7 in Example 7 of this invention; Figure 10 The hydrogen NMR spectrum of the target product P8 in Example 8 of this invention; Figure 11-18 The fluorescence emission spectra of the solutions of the target products P1-P8 in Examples 1-8 of the present invention are shown. Figure 19 The images show the 1H NMR spectra of the target product P1 before and after degradation in Example 10 of this invention. Detailed Implementation
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Please see the appendix Figure 1 - Appendix Figure 19 This invention provides a biodegradable and recyclable fluorescent polyacetal and its preparation method. The main raw materials and reagents used in the following examples and comparative examples are as follows. Unless otherwise specified, all reagents are commercially available analytical grade or higher grade products.
[0027] The diols and aldehyde monomers used in the embodiments of this invention are all commercially available products, specifically including: 1,6-hexanediol (CAS No.: 629-11-8), 1,4-butynediol (CAS No.: 110-65-6), polyethylene glycol 400 (CAS No.: 25322-68-3), 2,5-furandiethanol (CAS No.: 1883-75-6); heptanal (CAS No.: 111-71-7), benzaldehyde (CAS No.: 100-52-7), 4-fluorobenzaldehyde (CAS No.: 459-57-4), 2-pyridinecarboxaldehyde (CAS No.: 1121-60-4), and 3-methoxy-4-hydroxybenzaldehyde (CAS No.: 121-33-5).
[0028] The catalysts and buffers used in the embodiments of this invention specifically include: sulfonic acid-functionalized silica (silica-supported sulfonicacid, particle size 40-63 μm, loading 1.0-1.5 mmol / g), tributylamine (CAS No.: 102-82-9), anhydrous stannous chloride (CAS No.: 7772-99-8), N,N-dimethylaniline (CAS No.: 121-69-7), aluminum trifluoromethanesulfonate (CAS No.: 74974-61-1), 1,1,3,3-tetramethylguanidine (CAS No.: 80-70-6), and dodecylbenzenesulfonic acid (CAS No.: The following reagents were used: 27176-87-0, triphenylphosphine (CAS No.: 603-35-0), 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (CAS No.: 84-58-2), imidazole (CAS No.: 288-32-4), palladium(II) acetate (CAS No.: 3375-31-3), quinoline (CAS No.: 91-22-5), sulfuric acid (CAS No.: 7664-93-9), N,N-diisopropylethylamine (CAS No.: 7087-68-5), triphenylmethyltetrafluoroborate (CAS No.: 341-02-6), and 4-methylquinoline (CAS No.: 491-35-0). Solvents used in the reactions and post-treatments, such as toluene and dichloromethane, were commercially available analytical grade reagents.
[0029] Preparation example: A general method for the synthesis of polyacetals This preparation example provides a general method for preparing high molecular weight polyacetals with fluorescent and degradable properties. This method is applicable to all substrate combinations described in this invention and specifically includes the following steps: (1) Feeding and Mixing: In a reaction vessel, add one or more hydroxyl-containing polyols (substrate A) and one or more aldehyde-containing compounds (substrate B). The molar ratio of the hydroxyl groups in substrate A to the aldehyde groups in substrate B is controlled at 1–50:1–25. If necessary, an organic solvent (such as tetrahydrofuran, dichloromethane, toluene, etc.) may be selectively added, with the solvent amount being 50 wt%–10000 wt% of the total mass of the reactants, or bulk polymerization may be carried out without using a solvent.
[0030] (2) Catalyst addition: Add an acid catalyst and an alkaline buffer to the above mixture. The amount of acid catalyst is 0.01wt% to 5wt% of the total mass of the reaction system; the molar ratio of acid catalyst to alkaline buffer is controlled at 5 to 100:1 to 10000.
[0031] (3) Polymerization reaction: The reaction system is heated to 20°C to 200°C under stirring. The reaction is carried out under acid-base synergistic catalysis for 10 min to 72 h. During the reaction, byproduct water is removed by physical means (such as high temperature, azeotropic distillation or molecular sieve adsorption) to shift the equilibrium of the acetalization reaction toward the product.
[0032] (4) Post-treatment and purification: After the reaction is complete, add an alkaline solution (such as sodium hydroxide solution) to adjust the pH of the reaction solution to neutral and stir evenly. Then wash with water or a weak alkaline solution and extract with an organic solvent. Collect the organic phase, dry it with a drying agent (such as anhydrous sodium sulfate), evaporate the solvent to remove it, and finally remove unreacted monomers and impurities by vacuum distillation to obtain the target polyacetal product.
[0033] Example 1: This example provides a method for preparing aliphatic polyacetal P1, comprising the following steps: Under an argon atmosphere, 0.236 g of aliphatic diol 1,6-hexanediol and 0.228 g of aliphatic aldehyde heptanal are added to a reaction vessel and stirred until homogeneous. Then, 10 mg of heterogeneous protic acid catalyst sulfonic acid-functionalized silica and 0.7 mL of organic base buffer tributylamine are added. The mixture is heated to 160 °C and reacted for 24 h with stirring. The byproduct water is removed by high temperature. After the reaction is complete, sodium hydroxide solution is added to adjust the pH of the reaction solution to neutral. The mixture is stirred for 2 min, washed with water or a weakly alkaline solution, and then extracted twice. The organic phase is collected, dried overnight with a desiccant, the solvent is evaporated, and finally purified by vacuum distillation. The target product P1 is obtained with a yield of 83% and a number average molecular weight of [missing information]. weight-average molecular weight polydispersion coefficient .
[0034] Example 2: This example provides a method for preparing polyacetal P2 containing aromatic ring side groups, comprising the following steps: Under an argon atmosphere, 1,6-hexanediol (0.236 g) and the aromatic aldehyde benzaldehyde (0.212 g) are added to a reaction vessel and stirred until homogeneous. Then, anhydrous stannous chloride (15 mg) and N,N-dimethylaniline (1.0 mL) are added as Lewis acid catalysts. The mixture is heated to 180°C and reacted for 24 h with stirring. The byproduct water is removed by adsorption using a molecular sieve. After the reaction is complete, sodium hydroxide solution is added to adjust the pH of the reaction solution to neutral. The mixture is stirred for 2 min, washed with water or a weakly alkaline solution, and then extracted twice. The organic phase is collected, dried overnight with anhydrous sodium sulfate, the solvent is evaporated, and finally purified by vacuum distillation. The target product P2 is obtained with a yield of 93% and a number average molecular weight of [missing information]. weight-average molecular weight polydispersion coefficient .
[0035] Example 3: This example provides a method for preparing a high molecular weight polyacetal P3 containing fluorinated aromatic side groups, comprising the following steps: Under an argon atmosphere, 1,6-hexanediol (0.236 g) and the halogenated aromatic aldehyde 4-fluorobenzaldehyde (0.248 g) are added to a reaction vessel and stirred until homogeneous. Then, a strong Lewis acid catalyst, aluminum trifluoromethanesulfonate (45 mg), and a strong organic base buffer, 1,1,3,3-tetramethylguanidine (1.5 mL), are added. The mixture is heated to 140°C and reacted for 24 h with stirring. The byproduct water is removed by high temperature. After the reaction is complete, sodium hydroxide solution is added to adjust the pH of the reaction solution to neutral. The mixture is stirred for 2 min, washed with water or a weakly alkaline solution, and then extracted twice. The organic phase is collected, dried overnight with anhydrous sodium sulfate, the solvent is evaporated, and finally purified by vacuum distillation. The target product P3 is obtained with a yield of 88% and a number average molecular weight of [missing information]. weight-average molecular weight polydispersion coefficient .
[0036] Example 4: This example provides a method for preparing polyacetal P4 containing heterocyclic side groups, comprising the following steps: Under an argon atmosphere, 1,6-hexanediol (0.236 g) and the heterocyclic aldehyde 2-pyridinecarboxaldehyde (0.214 g) are added to a reaction vessel and stirred until homogeneous. Then, the organic protic acid catalyst dodecylbenzenesulfonic acid (15 mg) and the organic base buffer triphenylphosphine (50 mg) are added. Under stirring, the mixture is heated to 120°C and reacted for 24 h. The byproduct water is removed by adsorption using a molecular sieve. After the reaction is complete, sodium hydroxide solution is added to adjust the pH of the reaction solution to neutral. The mixture is stirred for 2 min, washed with water or a weakly alkaline solution, and then extracted twice. The organic phase is collected, dried overnight with anhydrous sodium sulfate, the solvent is evaporated, and finally purified by vacuum distillation. The target product P4 is obtained with a yield of 87% and a number average molecular weight of [missing information]. weight-average molecular weight polydispersion coefficient .
[0037] Example 5: This example provides a method for preparing polyacetal P5 containing multifunctional aromatic side groups, using a solvent-assisted reaction system, including the following steps: Under an argon atmosphere, 1,6-hexanediol (0.236 g) and the multifunctional aromatic aldehyde 3-methoxy-4-hydroxybenzaldehyde (0.304 g) are added to a reaction vessel, followed by the addition of toluene (2 mL) as an organic solvent. After stirring, the organic catalyst 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (20 mg) and the organic base buffer imidazole (15 mg) are added. The mixture is heated to 150°C with stirring and reacted for 24 h. The byproduct water is removed by adsorption using a molecular sieve. After the reaction is complete, sodium hydroxide solution is added to adjust the pH of the reaction solution to neutral, and the mixture is stirred for 2 min. The solution is washed with water or a weakly alkaline solution, and then extracted twice. The organic phase is collected, dried overnight with anhydrous sodium sulfate, the solvent is evaporated, and finally purified by vacuum distillation. The target product P5 is obtained with a yield of 82% and a number average molecular weight of [missing information]. weight-average molecular weight polydispersion coefficient .
[0038] Example 6: This example provides a method for preparing polyacetal P6 with unsaturated bonds in the main chain, comprising the following steps: Under an argon atmosphere, 0.172 g of the unsaturated diol butynediol and 0.228 g of the aliphatic aldehyde heptanal are added to a reaction vessel and stirred until homogeneous. Then, 30 mg of a palladium(II) complex catalyst and 1.0 mL of an organic base buffer quinoline are added. The mixture is heated to 140 °C and reacted for 24 h with stirring. The byproduct water is removed by high temperature. After the reaction is complete, sodium hydroxide solution is added to adjust the pH of the reaction solution to neutral. The mixture is stirred for 2 min, washed with water or a weakly alkaline solution, and then extracted twice. The organic phase is collected, dried overnight with anhydrous sodium sulfate, the solvent is evaporated, and finally purified by vacuum distillation. The target product P6 is obtained with a yield of 85% and a number average molecular weight of [missing information]. weight-average molecular weight polydispersion coefficient .
[0039] Example 7: This example provides a method for preparing high molecular weight polyacetal P7 based on polyether glycol, comprising the following steps: Under an argon atmosphere, polyethylene glycol 400 (0.800 g) and aliphatic aldehyde heptanal (0.228 g) are added to a reaction vessel and stirred until homogeneous. Then, sulfuric acid (2 mg) and diisopropylethylamine (1.5 mL) are added as an inorganic protic acid catalyst. The mixture is heated to 180°C and reacted for 24 h with stirring. The byproduct water is removed by high temperature. After the reaction is complete, sodium hydroxide solution is added to adjust the pH of the reaction solution to neutral. The mixture is stirred for 2 min, washed with water or a weakly alkaline solution, and then extracted twice. The organic phase is collected, dried overnight with anhydrous sodium sulfate, the solvent is evaporated, and finally purified by vacuum distillation. The target product P7 is obtained with a yield of 90% and a number average molecular weight of [missing information]. weight-average molecular weight polydispersion coefficient .
[0040] Example 8: This example provides a method for preparing polyacetal P8 with a heterocyclic main chain, comprising the following steps: Under an argon atmosphere, 0.256 g of the heterocyclic diol 2,5-furandiethanol and 0.228 g of the aliphatic aldehyde heptanal are added to a reaction vessel and stirred until homogeneous. Then, 15 mg of the organic salt catalyst triphenylmethyltetrafluoroborate and 1 mL of the organic base buffer 4-methylquinoline are added. The mixture is heated to 110 °C and reacted for 24 h with stirring. The byproduct water is removed by adsorption using a molecular sieve. After the reaction is complete, sodium hydroxide solution is added to adjust the pH of the reaction solution to neutral. The mixture is stirred for 2 min, washed with water or a weakly alkaline solution, and then extracted twice. The organic phase is collected, dried overnight with anhydrous sodium sulfate, the solvent is evaporated, and finally purified by vacuum distillation. The target product P8 is obtained with a yield of 89% and a number average molecular weight of [missing information]. weight-average molecular weight polydispersion coefficient .
[0041] Based on the design of the foregoing embodiments, in order to fully demonstrate the key role of the acid-base synergistic catalytic system in the synthesis of high molecular weight, narrow distribution polyacetals, and its advantages over existing technologies, the following comparative examples are designed.
[0042] Comparative Example 1: Compared with Example 1, the difference is that the organic base buffer tributylamine was not added, and only sulfonic acid functionalized silica was used as a catalyst. The other reaction raw materials and conditions were the same as in Example 1.
[0043] Design objective: To demonstrate that alkaline buffers are key to obtaining high molecular weight products by suppressing side reactions and chain degradation under acidic conditions.
[0044] Comparative Example 2: Compared with Example 1, the difference is that no acidic catalyst sulfonic acid functionalized silica was added, only tributylamine was added, and the rest of the reaction raw materials and conditions were the same as in Example 1.
[0045] Design objective: To demonstrate that an acidic catalyst is a necessary condition for initiating carbonyl activation and acetalization reactions, and that polymerization cannot be initiated by base alone.
[0046] Comparative Example 3: Compared with Example 1, the difference is that the catalytic system is changed. Instead of using sulfonic acid functionalized silica and tributylamine, an equimolar amount of p-toluenesulfonic acid (PTSA) is used as a single catalyst. All other reaction raw materials and conditions are the same as in Example 1.
[0047] Design objective: Compared with the single strong organic acid catalytic systems commonly used in existing technologies, this invention highlights the advantages of synergistic catalysis in improving molecular weight and yield.
[0048] Comparative Example 4: Compared with Example 2, the difference is that the organic base buffer N,N-dimethylaniline was not added, and only anhydrous stannous chloride was used as a catalyst. The other reaction raw materials and conditions were the same as in Example 2.
[0049] Design objective: To verify that alkaline buffers also have an indispensable synergistic stabilizing effect in Lewis acid (metal salt) catalytic systems.
[0050] Test Example 1: Polymer Structure Characterization and Verification of Acetal Bond Formation 1. Experiment Description The polymer samples P1-P8 prepared in Examples 1 to 8 were subjected to proton NMR spectroscopy to confirm the formation of acetal bonds (-O-CH(R)-O-) and the integrity of the polymer backbone structure.
[0051] The test solvent used was deuterated chloroform ( ) or deuterated dimethyl sulfoxide ( All of them contain tetramethylsilane as an internal standard ( Take approximately 10-15 mg of the dried polymer sample to be tested, dissolve it completely in 0.6 mL of deuterated solvent, and transfer it to a standard NMR tube. The test temperature is 298 K, the number of scans is 16 or 32, and the spectral width is set to the normal range. Chemical shift calibration is performed using the TMS peak or solvent residue peak as a reference during data processing.
[0052] 2. Experimental Data The characteristic 1H NMR spectra of the products from each embodiment are summarized in the table below. The table mainly lists the characteristic methylene proton chemical shifts and their splitting patterns used to determine the formation of the acetal structure, as well as the chemical shifts of the characteristic methylene groups in the diol portion.
[0053] Table 1 Summary of characteristic peak data of P1-P8 NMR 1H spectra in Examples 3. Results Analysis and Conclusions The results of nuclear magnetic resonance hydrogen spectroscopy confirmed the successful construction of the target polyacetal structure in all embodiments.
[0054] The data distribution shows a clear structural correlation in the proton chemical shifts of the acetal methylene groups formed from different aldehyde monomers. In systems using aliphatic aldehydes (heptanal) as raw materials (P1, P6, P7, P8), the acetal proton signals are concentrated in the 4.59–4.71 ppm region, exhibiting a triplet split due to coupling with the ortho-methylene group. In contrast, in systems using aromatic or heterocyclic aldehydes as raw materials (P2, P3, P4, P5), due to the deshielding effect of the aromatic or heterocyclic rings, the acetal proton signals shift significantly to the lower field, reaching the 5.39–5.63 ppm region, and exhibit a singlet shape. No obvious aldehyde characteristic peaks (typically located at 9.5–10.0 ppm) were observed in any of the spectra, indicating complete monomer conversion.
[0055] Based on the reaction mechanism of this invention, this polymerization reaction is a typical acid-catalyzed nucleophilic addition-elimination process. The acidic catalyst protonates or coordinates the carbonyl carbon of the aldehyde group, reducing its electron cloud density, thereby promoting the nucleophilic attack of the oxygen atom of the diol hydroxyl group, forming a hemiacetal intermediate, which then undergoes dehydration to form an acetal bond. However, the acetal bond itself is highly sensitive to acids, readily undergoing reverse hydrolysis or acidolysis in strongly acidic environments, leading to polymer chain breakage and making it difficult to obtain high molecular weight products.
[0056] The alkaline buffer and acidic catalyst introduced in this technical solution constitute a synergistic catalytic system. This system maintains a suitable acid strength window in the reaction medium by controlling the molar ratio of the acid and base components. The alkaline component effectively neutralizes locally excessively strong free acid sites, inhibiting the acid-catalyzed degradation of the already formed acetal backbone at high temperatures, resulting in a chain growth reaction rate significantly exceeding the chain degradation rate. The clear acetal characteristic peaks and baseline flatness in Table 1 indicate that this synergistic system effectively ensures the chemical stability of the polymer backbone while shifting the condensation reaction equilibrium towards polymer formation, thus achieving the controllable preparation of structurally well-defined, high-molecular-weight polyacetals.
[0057] Test Example 2: Determination of Polymer Molecular Weight and Molecular Weight Distribution 1. Experiment Description The number-average molecular weights of the products obtained in Examples 1-8 and Comparative Examples 1-4 were determined by gel permeation chromatography. ), weight-average molecular weight ( ) and polydispersity index ( ).
[0058] The testing instrument used was a high-performance liquid chromatography (HPLC) system equipped with a differential refractive index detector. Two PLgel 5μm MIXED-C columns (300×7.5mm) were used in series to cover a wide molecular weight range. The mobile phase was chromatographic grade tetrahydrofuran, the flow rate was set to 1.0 mL / min, and the column oven temperature was controlled at 35℃.
[0059] The sample preparation procedure is as follows: Accurately weigh approximately 3-5 mg of the dried polymer sample and place it in a sample vial. Add 1.0 mL of tetrahydrofuran solvent. Allow the sample to stand or shake at room temperature for at least 4 hours to ensure complete dissolution. Filter the dissolved sample solution through a 0.45 μm polytetrafluoroethylene syringe filter to remove any trace amounts of insoluble matter or dust particles. The injection volume is set to 50 μL.
[0060] Data acquisition and processing were performed using the instrument's accompanying workstation software. The molecular weight calibration curve was established using a set of narrow-distribution polystyrene standards, with a molecular weight range of 500 g / mol to 3,000,000 g / mol. The relative molecular weight and distribution were calculated by comparing the sample wash volume with the standard curve. The yield was calculated based on the ratio of the final dried product mass to the theoretical yield.
[0061] 2. Experimental Data The molecular weight and yield test results of each embodiment and comparative example are summarized in Table 2.
[0062] Table 2 Summary of GPC test data and yield of products from the examples and comparative examples. 3. Results Analysis and Conclusions Table 2 shows the influence of the acid-base synergistic catalytic system on the molecular weight growth and distribution control of acetal polymerization.
[0063] Examples 1-8 all successfully yielded high molecular weight polyacetal products after introducing specific acid-base catalyst combinations. Among them, the number-average molecular weights of the aliphatic and aromatic systems (…) The polydispersity index (PDI) is generally distributed between 2.4 kg / mol and 14.4 kg / mol. The yield remained above 80% when the stoichiometry was controlled within a narrow range of 1.26 to 1.92. This indicates that the system can adapt to diol and aldehyde monomers with different structures and achieve effective chain growth.
[0064] In contrast, the test results of the comparative examples showed significant differences. Comparative Examples 1 and 4 removed the alkaline buffer from the reaction system, retaining only the acidic catalyst. The results showed that... The yield dropped sharply to below 1.1 kg / mol, and the polydispersity index broadened to above 3.0, resulting in low yield. This phenomenon is attributed to the chemical properties of the acetal bond: the acetal bond exhibits high reversibility and instability under acidic conditions. Although strong acids can activate carbonyl groups to initiate nucleophilic addition, in the later stages of polymerization or at high temperatures, excessively strong acidic environments catalyze the acidolysis or reverse hydrolysis of the already formed polymer chains, leading to the breakage of long chains into oligomers, limiting the increase in molecular weight and exacerbating side reactions.
[0065] In Comparative Example 2, the reaction failed to start and the yield was extremely low when only an alkaline component was added without an acid catalyst. This confirms the necessity of acidic sites for the electrophilic activation of the carbonyl carbon; a purely alkaline environment cannot induce an effective attack of the diol hydroxyl group on the aldehyde group.
[0066] Comparative Example 3 used a traditional single organic strong acid catalyst, although it yielded a product with a certain molecular weight ( However, compared to Example 1, its molecular weight is lower and its distribution is wider ( The yield was also lower than that of the synergistic system. This is consistent with the conclusion reported in existing technologies that direct acetalization usually yields low molecular weight polymers. A single strong acid is unlikely to establish a balance between catalyzing polymerization and inhibiting degradation.
[0067] In summary, the acid-base synergistic catalytic system constructed in this invention initiates polymerization through an acidic component and regulates the microenvironment acidity using an alkaline component, forming a dynamic equilibrium mechanism of "acid-driven - base-buffered". This mechanism effectively suppresses side reactions such as acid-induced chain scission while ensuring reactivity, thereby achieving controllable construction of acetal polymer molecular weight and improved yield, solving the technical bottleneck of difficulty in increasing molecular weight in traditional acetal polymerization.
[0068] Test Example 3: Polymer Photoluminescence / Fluorescence Performance Test 1. Experiment Description Steady-state fluorescence emission spectra of polymers P1-P8 prepared in Examples 1-8 were measured using a fluorescence spectrophotometer.
[0069] Sample preparation: Accurately weigh approximately 10 mg of the dried and purified polymer sample from each example and place it in a 10 mL volumetric flask. Add chromatographic grade dichloromethane to dissolve and dilute to volume to prepare a homogeneous solution with a mass concentration of 1.0 mg / mL.
[0070] Test conditions: Place the sample solution in a standard quartz fluorescence cuvette. Set the excitation wavelength ( The wavelength was 365 nm, the excitation and emission slit widths were both 5.0 nm, the scan rate was 1200 nm / min, and the photomultiplier tube voltage was 700 V. Emission spectrum data were acquired in the range of 380 nm to 800 nm. Simultaneously, the macroscopic emission color of the sample solution was observed and recorded under ultraviolet light illumination.
[0071] 2. Experimental Data The fluorescence spectral test data and macroscopic observation results of the product solutions of each embodiment are summarized in Table 3.
[0072] Table 3 Summary of photoluminescence performance data of polymer solutions P1-P8 in Examples 3. Results Analysis and Conclusions Fluorescence spectroscopy results show that the polyacetal material prepared in this invention exhibits significant photoluminescence properties, and the emitted colors cover a wide spectral range from blue-violet to orange-red.
[0073] Analysis of the relationship between structure and performance: Polymers with aliphatic segments as the main chain exhibit shorter wavelength emission, displaying typical blue-violet light. The luminescence mechanism of these non-conjugated backbone polymers differs from traditional conjugated double bond luminescence, attributing it to the electronic cluster structure formed by the acetal oxygen atoms and spatial folding, i.e., cluster luminescence. The lone pair electrons of the oxygen atoms in the acetal bond undergo transitions with neighboring groups, forming an extended electronic delocalization system through spatial interactions in the polymer chain aggregate state or concentrated solution, thereby inducing fluorescence emission.
[0074] The introduction of aromatic or heterocyclic side groups results in a significant redshift in emission wavelength. The emission peaks of P2 and P3 redshift to the 420-430 nm region. This redshift is even more pronounced when side groups with strong push-pull electron effects or heteroatoms are introduced. For example, P8, containing a furan ring, emits at 493 nm, while P4, containing a pyridine ring, further redshifts to 585 nm. This redshift is due to the aromatic / heterocyclic side groups expanding the conjugation of the system and potentially causing intramolecular charge transfer with the acetal oxygen atom in the main chain, thus reducing the energy level difference between the excited and ground states.
[0075] Furthermore, the differences in fluorescence intensity data reflect the influence of different side-group structures on the nonradiative transition pathways of excited states. The introduction of heteroatoms may increase the probability of intersystem crossing or change the aggregation mode, thereby modulating the quantum yield.
[0076] In summary, the polyacetal synthesized through acid-base synergistic catalysis in this technical solution not only possesses high molecular weight characteristics but also inherently possesses tunable fluorescence functionality. By simply altering the chemical structure of the aldehyde monomer, the full spectrum of the material's luminescence color can be adjusted without changing the polymerization backbone formation mechanism. This structure-property designability, combined with the inherent acid-responsive degradation characteristics of acetal bonds, makes this type of material promising for applications in degradable bioimaging probes, anti-counterfeiting coatings, and smart responsive materials.
[0077] Test Example 4: Chemical Cyclic Degradation and Raw Material Recovery Performance Test 1. Experiment Description Acid-catalyzed hydrolysis experiments were conducted on the polyacetal samples (P1-P8) prepared in Examples 1-8 to evaluate their degradation performance and raw material recovery efficiency.
[0078] The experimental steps are as follows: Accurately weigh approximately 1.0 g of the dried polymer sample (record the mass as follows). The mixture was placed in a 50 mL single-necked flask. 20 mL of 1 M hydrochloric acid aqueous solution was added. For some highly hydrophobic samples containing aromatic rings or long-chain alkyl groups, an additional 2 mL of tetrahydrofuran was added as a solubilizer to improve dispersibility. The reaction system was magnetically stirred at 25 °C for 24 hours.
[0079] After the reaction is complete, observe the disappearance of the solid. Transfer the reaction solution to a separatory funnel and extract with dichloromethane. Combine the organic phases, wash successively with saturated sodium bicarbonate solution and saturated brine, dry with anhydrous sodium sulfate, and filter. Remove the solvent from the filtrate using a rotary evaporator; the resulting oily or solid residue is the recovered monomer mixture. Place the residue in a vacuum drying oven and dry further to constant weight, then weigh the recovered product. ).
[0080] The structure of the recovered product was analyzed using proton nuclear magnetic resonance spectroscopy and compared with the original monomer spectrum.
[0081] The formula for calculating the mass recovery rate is: .
[0082] 2. Experimental Data The degradation status and mass recovery rate test results of the samples in each embodiment are shown in Table 4.
[0083] Table 4. Test data on acid degradation and raw material recovery of P1-P8 in Examples. 3. Results Analysis and Conclusions Degradation experiments show that the polyacetal material prepared by this technical solution has excellent chemical degradability and raw material recyclability under mild acidic conditions.
[0084] The degradation phenomena showed that all polymer samples (P1-P8) completely dissolved after 24 hours of treatment with 1M hydrochloric acid, transforming into clear solutions with no visible polymer solid residue. This confirms that the acetal bonds (-O-CHR-O-) in the main chain are highly sensitive to acidic environments. In the presence of excess water and under acid catalysis, the acetal bonds undergo protonation and breakage, shifting the reaction equilibrium entirely in the reverse direction (i.e., the hydrolysis direction), leading to the rapid depolymerization of the polymer chains into small molecule diols and aldehydes.
[0085] The fluctuations in recovery rates reflect the differences in the physicochemical properties of different monomer structures. Systems dominated by long-chain aliphatic monomers (such as P1 and P6) have high partition coefficients of their hydrolysis products in organic solvents, resulting in mass recoveries above 94%, close to the theoretical value. For systems containing strongly polar groups or water-soluble segments, the recovery rates are lower. For example, the recovery rate of Example P7 (based on PEG-400) is only 77.0%, which is not due to incomplete degradation, but rather to the high solubility of the hydrolysis product polyethylene glycol in the aqueous phase, leading to physical losses during extraction. The recovery rate of Example P4 (containing a pyridine ring) (85.2%) is low, presumably because the pyridine nitrogen atom protonates to form a salt under strong acid conditions, increasing the product's water solubility and thus reducing the extraction efficiency of the organic phase.
[0086] Nuclear magnetic resonance (NMR) 1H NMR spectroscopy further confirmed the completeness of the degradation at the microscopic level. In the spectrum of the recovered products, the polymer-specific acetal-methyl proton peak (…) The aldehyde group characteristic peaks completely disappeared, and were replaced by the characteristic peaks of the aldehyde group in the raw material. The characteristic shifts of the diol hydroxyl group and the methylene group were regressed. The spectral fingerprint region highly overlapped with the original monomer, indicating that the chemical structure of the degradation product did not undergo side reactions or denaturation.
[0087] In summary, this invention utilizes the reversible equilibrium characteristic of acetal bonds in an "acidic synthesis-acidic degradation" process. By introducing an alkaline buffer during the synthesis stage to inhibit acidolysis and obtain high molecular weight polymers, and then using an excess of strong acid during the degradation stage to disrupt the equilibrium and achieve complete depolymerization, this closed-loop chemical cycle mechanism not only achieves the degradation and reduction of waste polymers but also efficiently recovers high-value-added chemical monomers, providing a feasible technical path for solving the environmental pollution problems of thermosetting or recalcitrant polymers.
[0088] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A biodegradable and recyclable fluorescent polyacetal, characterized in that, The reaction mixture comprises the following components polymerized under acid-base synergistic catalysis: Component A: a hydroxyl-containing polyol, whose molecular structure contains at least two hydroxyl groups; Component B: an aldehyde-containing compound, whose molecular structure contains at least one aldehyde group; Catalyst system: composed of an acid catalyst and a base buffer; wherein, the molar ratio of the hydroxyl groups in Component A to the aldehyde groups in Component B is 1–50 : 1–25; the amount of the acid catalyst is 0.01 wt%–5 wt% of the total mass of the reaction system; the molar ratio of the acid catalyst to the base buffer is 5–100 : 1–10000; The acid catalyst is selected from one or more of the following: sulfonic acid functionalized silica, anhydrous stannous chloride, aluminum trifluoromethanesulfonate, dodecylbenzenesulfonic acid, 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, palladium(II) acetate, sulfuric acid, or triphenylmethyltetrafluoroborate; the base buffer is selected from one or more of the following: tributylamine, N,N-dimethylaniline, 1,1,3,3-tetramethylguanidine, triphenylphosphine, imidazole, quinoline, N,N-diisopropylethylamine, or 4-methylquinoline. The polyacetal has a number-average molecular weight of 1,000 to 50,000 g / mol and exhibits fluorescence characteristics with an emission wavelength of 350 nm to 680 nm under 365 nm excitation light. Component A is selected from 1,6-hexanediol, 1,4-butynediol, polyethylene glycol 400, or 2,5-furandiethanol; Component B is selected from heptanal, benzaldehyde, 4-fluorobenzaldehyde, 2-pyridinecarboxaldehyde, or 3-methoxy-4-hydroxybenzaldehyde.
2. A method for preparing a biodegradable and recyclable fluorescent polyacetal, characterized in that, The method for preparing the biodegradable and recyclable fluorescent polyacetal as described in any one of claims 1 comprises the following steps: (1) Feeding and mixing: Mix component A and component B evenly; (2) Catalyst addition: Add the acid catalyst and the base buffer to the mixture in step (1); (3) Polymerization reaction: Under stirring conditions, the reaction system is heated to 20°C to 200°C for 10 min to 72 h, and the by-product water is removed during the reaction. (4) Post-processing: After the reaction is completed, an alkaline solution is added to adjust the pH of the reaction solution to neutral. The target product is obtained after washing, extraction, drying and vacuum distillation.
3. The method for preparing a biodegradable and recyclable fluorescent polyacetal according to claim 2, characterized in that, In step (1), an organic solvent is also added. The organic solvent is selected from one or more of tetrahydrofuran, dichloromethane, acetonitrile, dimethylformamide or toluene. The amount of the organic solvent is 50 wt% to 10000 wt% of the total mass of the reactants.
4. The method for preparing a biodegradable and recyclable fluorescent polyacetal according to claim 2, characterized in that, In step (3), the byproduct water can be removed by high-temperature evaporation, azeotropic distillation or molecular sieve adsorption.
5. The method for preparing a biodegradable and recyclable fluorescent polyacetal according to claim 2, characterized in that, In step (4), the alkaline solution is a sodium hydroxide solution; the washing uses water or a saturated sodium bicarbonate solution; and the extraction uses dichloromethane.
6. The method for preparing a biodegradable and recyclable fluorescent polyacetal according to claim 2, characterized in that, In step (3), the polymerization reaction is carried out in an inert gas atmosphere composed of argon or nitrogen; In step (4), the specific operation of the post-processing is as follows: after the reaction is completed, sodium hydroxide solution is added to the reaction system to adjust the pH value to neutral, the organic phase is collected after standing and layering or extraction, and then washed with water or weak alkaline solution in sequence. After drying with anhydrous sodium sulfate overnight, the solvent and unreacted monomers are removed by vacuum distillation to obtain the degradable and recyclable fluorescent polyacetal.
Citation Information
Patent Citations
process for preparing high molecular weight polyketals
FR1361204A
Method for preparing polyacetals and polyketals by emulsion polymerization
US4374953A
